ABC Analysis of an Aerospace Business Case on ALM Technologies in Aerospace and Defence Supply Chain. Issue 1 (March 2019) - Kemsaram, Narsimlu; Maley, Kishore Kumar; Mahadevan, Raghunandan
This article provides an analysis of an aerospace business case on additive layer manufacturing (ALM) process. Using activity-based costing (ABC), we can breakdown the cost drivers and understand the cost levers associated with ALM process. This can help us in finding the innovative ways to enhance the ALM process operation's efficiency. We have considered an aircraft bracket manufacturing using the direct metal laser sintering process as a business case for our ABC analysis on additive layer manufacturing technologies in aerospace and defence supply chain. The additive layer manufactured components associated cost can be divided into design cost, production cost, post-processing cost and qualification cost. Each step in the additive manufacturing process performs at one organisation or across a supply chain based on the various internal and external suppliers. Also, there are overhead costs associated with each step of this additive manufacturing process. This article explains the cost involved in the component design and its relevance to supply chain. It explains the cost involved in the component production such as materials cost, machine set-up cost, machine runtime cost and final build plate removal cost. It also explains the cost involved in the post-processing such as heat-treating cost, machining cost and surface finish cost. The component process cost is required to qualify based on its end use. The component qualification cost is required to add significantly to the component overall cost including the labour cost and computer tomography scan cost. The overhead cost is depending on the individual operation and it assigns these costs appropriately. It computes the ABC for an aerospace bracket and concludes with analysis to make a convinceable business case for the use of innovative technology and to enable to identify the cost of drivers and levers, so it can drive business with more efficiently.